Microstructural Analysis of Nickel Superalloy MAR-M247 - Petr Jonsta; Zdenek Jonsta; Katerina Konecna; Miriam Gabcova; Karel Hrbacek (Communications - Scientific letters of the University of Zilina, 2012)
This paper presents the results of a microstructural phase analysis of the nickel superalloy MAR M247 after casting and different modes of dissolving annealing in the range of 900°C – 1240°C with cooling in water. The alloy in question presents a polycrystalline nickel creepresistant alloy usable especially for highly stressed components in the aerospace and rocket industries. The analysis was performed using a JEOL JSM 6490LV scanning electron microscope with an Oxford Inca x-act x-ray microanalyzer. The presence of minority phases was identified. The study is focused on their possible changes after the application of different modes of thermal treatment.